KEMAMPUAN MENULIS PARAGRAF ARGUMENTASI PADA SISWA KELAS X A SMANEGERI 1 MENYUKE - Seriati, Seriati (Universitas Tanjungpura, 2018)
Writing skill for Argumentation Paragraph for students in SMA N 1 Menyuke, regency on the tenth grade in secondA semeste.Â The purpose of this research was described students writing skill for argumentation paragraph based on the aspect observation from the unity of paragraph, coherence of paragraph, development of paragraph. This research used descriptive in qualitative method. The instrument of this research was written test for argumentation paragraph. The result of this research were 95% for the unity of paragraph, 44,37% for coherence of paragraph, 51,87%.The general conclusion of this research showed students writing skill in argumentation paragraph for students on the tenth grade in SMA N 1 Menyuke Landak regency in second semester 2014/2015 achieved the score 63,54% with ranges 56%-65% categorized poor to average, whether there are some aspect must be increase.